2012
DOI: 10.1002/pro.2150
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the structures and stabilities of coiled‐coil proteins containing hexafluoroleucine and t‐butylalanine provides insight into the stabilizing effects of highly fluorinated amino acid side‐chains

Abstract: Highly fluorinated analogs of hydrophobic amino acids are well known to increase the stability of proteins toward thermal unfolding and chemical denaturation, but there is very little data on the structural consequences of fluorination. We have determined the structures and folding energies of three variants of a de novo designed 4-helix bundle protein whose hydrophobic cores contain either hexafluoroleucine (hFLeu) or t-butylalanine (tBAla). Although the buried hydrophobic surface area is the same for all thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…[9][10][11][12][13] Simultaneously, minimizing changes in solute-solute packing upon mutations is desirable to ensure that protein structureand thus function -is preserved. 14,15 This is, however, difficult with the limited pool of canonical hydrophobic amino acids because their side chains differ in structure and volume. Fluorinated versions of those amino acids, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] Simultaneously, minimizing changes in solute-solute packing upon mutations is desirable to ensure that protein structureand thus function -is preserved. 14,15 This is, however, difficult with the limited pool of canonical hydrophobic amino acids because their side chains differ in structure and volume. Fluorinated versions of those amino acids, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Addressing this question is of high importance as the fluorine-labelled protein variant, and not the wild type, is used in in cellula NMR spectroscopy to report on the native structural and dynamical features of proteins in vivo. In this context, it has been shown that extensively fluorinated amino acids can be particularly effective in increasing protein stability 28 due to the increase in buried hydrophobic surface area as identified in structures solved by X-ray crystallography 29 . Kitevski-LeBlanc and co-workers have shown that 19 F enrichment in fluoro-phenyalanine labelled calmodulin results in an increasing protein disorder which can be diminished by a decreased level of fluorination 30 .…”
mentioning
confidence: 99%
“… 35 37 In contrast, in the most widely used direct analogue of a canonical α-amino acid, hexafluoroleucine (6 fluorines), the two trifluoromethyl groups are diastereotopic, exhibiting separate resonances, and each is coupled to the methine hydrogen, resulting in reduced peak intensity due to each trifluoromethyl group existing as a doublet (four total peaks observed). 18 , 38 41 …”
mentioning
confidence: 99%